Antimicrobial And Antioxidant Activities Of Endophytic Fungi Isolated From Curcuma Mangga, With Emphasize On Ceratobasidium ramicola IBRLCM127 - Abdul Rahman, Kharul Azmi Mu’azzam (2021)
Endophytic fungi isolated from medicinal herbs have been acknowledged as one of the potential sources for the development of natural product-based drug that might be able to solve the global problem of bacterial resistant to the commonly used antibiotics. This research was aimed to study the antimicrobial and antioxidant activity of fungal endophytes isolated from various parts of medicinal herb, Curcuma mangga.